(untitled) - Utterback, James M. (Havard, 1994)
A model for how innovation unsettles industries and firms, with histories of product developments - fluorescent lighting, computers, photography - and strategies for nurturing innovation. The text provides a strategy that should help companies become and remain industry leaders. It draws on the history of innovation by inventors and entrepreneurs, and develops a practical model for how innovation enters an industry, how firms respond, and how new and old players wrestle for dominance. The author asserts that existing organizations must consistantly abandon past success and embrace innovation, even when it undermines their traditional strengths
Keywords: Technological innovations,Đổi mới công nghệ,Industrial management,Quản lý công nghiệp; Management,Quản lý